Fast-ion energy resolution by one-step reaction gamma-ray spectrometry. (2nd March 2016) - Salewski, M.; Nocente, M.; Gorini, G.; Jacobsen, A.S.; Kiptily, V.G.; Korsholm, S.B.; Leipold, F.; Madsen, J.; Moseev, D.; Nielsen, S.K.; Rasmussen, J.; Stejner, M.; et al.
Abstract: The spectral broadening of γ -rays from fusion plasmas can be measured in high-resolution gamma-ray spectrometry (GRS). We derive weight functions that determine the observable velocity space and quantify the velocity-space sensitivity of one-step reaction high-resolution GRS measurements in magnetized fusion plasmas. The weight functions suggest that GRS resolves the energies of fast ions directly without the need for tomographic inversion for selected one-step reactions at moderate plasma temperatures. The D(p, γ ) 3 He reaction allows the best direct fast-ion energy resolution. We illustrate our general formalism using reactions with and without intrinsic broadening of the γ -rays for the GRS diagnostic at JET.